Peningkatan hasil belajar siswa materi usaha mempertahankan Republik Indonesia melalui model pembelajaran Snowball Throwing pada kelas IX.2 Smp Negeri Muara Beliti - Holili Holili (Universitas Negeri Malang, 2017)
This study aims to improve student learning outcomes of class IX.2 State Junior High School Muara Beliti on the material business to defend the Republic of Indonesia by using the Snowball throwing learning. The research method used is Classroom Action Research. The study was conducted in two cycles with each model cycle following the procedure: planning, action, observation, and reflection. The action of two cycles resulted in improving the quality of learning and improving the learning outcomes, the average completeness of students' learning cycle one 68.55% completeness 61.29%. Cycle two averages 80.1% completeness 90%. The end result of the two cycle action succeeded in improving the IPS learning outcomes.Keywords: Learning Outcome, Snowball throwing http://dx.doi.org/10.17977/um022v2i12017p025